ANALYZING AND MAPPING CSR IMPACT AND TRENDS: A BIBLIOMETRIC STUDY ON COMMUNITY EMPOWERMENT - Apriantoro, Muhamad Subhi; Pradana, Yoga Ferdira Wishnu; El Ashfahany , Afief; Setiana, Dadang (Ekonomi dan Bisnis: Berkala Publikasi Gagasan Konseptual, Hasil Penelitian, Kajian, dan Terapan Teori, 2023)
This research aims to evaluate and group to generate impact and direction regarding CSR, including a classification of topics to explain the current analysis results. The use of VOSviewer is also carried out in order to find out the analysis of the network of related documents and the relationship between authors. Analysis of appropriate and accurate bibliometric studies based on data from Scopus databases. This study can be a reference in analyzing citations, bibliographic coupling, co-authorship, and co-citation for CSR in community empowerment. The result shows that the most influential authors based on the publication were Okolo-Obasi En. and Uduji, J.I. with 11 documents each, the most relative affiliate related to the published documents were the University of South Australia, and the most productive country was the United Kingdom with 146 documents. There are three main research groups found, 1) CSR for Environment Sustainability, 2) Economic and social effects implications for Sustainable development, and 3) CSR for community development. The study presents a brief overview of the literature accessible to researchers working in this field and provides recommendations for future research.